PREDICTORS OF HOSPITAL COMPLICATIONS AND PROLONGED HOSPITALIZATION IN BYPASS PATIENTS: THE ROLE OF FREE FATTY ACIDS AND INSULIN RESISTANCE INDICES - Alexei Nikolaevich Sumin; Natalia Alexandrovna Bezdenezhnykh; Andrey Viktorovich Bezdenezhnykh; Anastasia Vyacheslavovna Osokina; Anastasia Alexandrovna Kuzmina; Anna Victorovna Sinitskaya; Olga Leonidovna Barbarash (Байкальский медицинский журнал)
Introduction. Often, carbohydrate metabolism disorders (type 2 diabetes mellitus, prediabetes) are detected in patients with severe coronary heart disease who are preparing for elective coronary bypass surgery. Insulin resistance can occur even in the absence of manifest disorders of carbohydrate metabolism and have its own influence on the course of coronary artery disease. With regard to the prognosis of coronary artery bypass grafting, the role of insulin resistance is not clearly defined, there are isolated reports on the relationship between the estimated indices of insulin resistance and free fatty acids and the number of postoperative complications of CABGPurpose of the study. To study the effect of carbohydrate metabolism disorders and insulin resistance indicators on the immediate results of coronary bypass grafting (CABG).Materials and methods. 383 consecutive patients who underwent CABG in 2011-2012 at the Research Institute of the KPSSZ were included, free fatty acids and fasting insulin in plasma were determined in all patients, insulin resistance indices HOMA-IR (Homeostasis Model Assessment of Insulin Resistance), QUICKI (Quantitative Insulin Sensitivity Chek) were calculated Index) and Revised-QUICKI, McAuley. A logistic regression analysis was performed to identify predictors of the composite endpoint of hospital stay after CABG >10 days or significant complication. Perioperative characteristics were analyzed in two cohort groups: group 1 - patients with a combined endpoint (CCT>10 days), n=291, and group 2 (n=92) without CCT.Results. In the CCT group, the median age was higher, and the proportion of women was 30% versus 14.1% (p=0.003). Patients of the 1st group (with CCT) had a higher percentage of type 2 diabetes mellitus (37.5% versus 17.4%, p<0.001, more people with obesity (p<0.001) and a higher percentage of combined operations (p =0.007) In group 1 (with CCT), the median of glucose (p=0.031), glycated hemoglobin HbA1c (p=0.009), free fatty acids (p=0.007) and Revised-QUICKI (p=0.020) was higher than In a binary regression, the predictors of the combined endpoint (significant complications or hospital stay after CABG >10 days) were female gender, age, left atrial size, and free fatty acids before surgery (p<0.001). per 1 mmol l, the probability of the endpoint increased by 255.9%, and with an increase in LA by 1 cm - by 219.5%, each year of age added 6.9% to the probability of the index event.For this model, the statistical significance was χ2 (2 ) = 38.337, p<0.001 The Nagelkerke R2 value was 0.336 (explaining 33.6% of the combined variance of the results) and the model correctly classified 78.5% of the cases. At the same time, fasting glucose, insulin, lipid levels, HOMA, QUICKI, Revised-QUICKI, McAuley indices did not show their relationship with the studied outcome.Conclusions: In the group with a complicated postoperative period of CABG, there were significantly more women, patients with DM 2, and obese individuals, there was a higher median of free fatty acids and the Revised-QUICKI index. Free fatty acids and type 2 diabetes mellitus were independent predictors of hospital complications or length of stay after CABG.